Psychological status during and after the preparation of a long-distance triathlon event in amateur athletes - Gosselin Boucher, V.; Caru, M.; Martin, S.-M.; Lopes, M.; Comtois, A. S.; Lalonde, F. (International Journal of Exercise Science, 2021)
Preparation for an endurance event among amateur athletes requires a major commitment on their part. Knowing amateur athletes` psychological characteristics during a training period should be a priority for coaches and athletes. The aim of our longitudinal study was to characterize the psychological profile of amateur athletes over a training period of six months prior to and after a long-distance triathlon. Thirty-two amateur athletes (13 females; 19 males; 1.5±1.3 years of experience) were recruited for this observational study. All participants (39±9.9 years old; weighs 73±12.9 kg; measure 172±10.2 cm) underwent a physical fitness assessment pre- and post 6-months of training, a monthly psychological questionnaire battery assessing mood, positive and negative affect, passion and motivation and, for some participants (n=5), an interview post event. Positive emotions increased until the sixth month, from 38.1±22.0 to 54.3±7.2 (Z=3.49, p<0.001, r=0.80). Participants were more harmonious (29.0±3.0) than obsessive (13.0±1.0) with their triathlon's passion (Z=4.91, p<0.001, r=0.85). Participants felt a high level of intrinsic motivation (15.9±1.76) and a low level of external motivation (4.9±1.08) about their triathlon training (p<0.05). The vigor score is the only sub scale that significantly changed from the 1st to the 6th month of training, and ranged between 21.4±10.6 and 28.1±4.1 (Z=2.0, p=0.046, r=0.46). This longitudinal observational study is the first to have explored athletes' psychological and emotional parameters over a training period of six months prior to a long-distance triathlon event and one month after. Thus, specific interventions and mental training can be structured around these important milestones.